Polityka państw bałtyckich wobec Rzeczypospolitej Polskiej i III Rzeszy na przełomie marca i kwietnia 1939 roku w ocenie wileńskiej ekspozytury oddziału II Sztabu Głównego Wojska Polskiego - Gajownik, Tomasz (Przegląd Wschodnioeuropejski, 2018)
Polish military intelligence had prepared a lot of analysis about political and military situations in the countries around the Republic of Poland. It was a kind of belaying towards potential Polish-German conflict. The issues of the Baltic States were interested a military intelligence’s field station in Vilnius. A few months before the Second World War has begun, Vilnius’s station prepared some analysis of domestic and foreign policy of Lithuania, Latvia and Estonia. One of them had discussed most important consequences of occupation of Klaipeda by German’s Wehrmacht. Additionally, in these documents, one can be read about multilateral policy of the Baltic Entente.